Understanding Additives - Müller, Bodo (Vincentz Network, 2019)
This book comprehensively discusses the mode of action, possible applications, and potential secondary effects of the most important coating additives in a single volume, presented in a textbook style. It considers practical needs, rapidly furnishing the reader with a solid foundation in these critical yet complex constituents of all paint formulas.